From mechanist to critical realist interrogations of academic literacy facilitation in extended degree curricula - Eybers, Oscar (South African Journal of Higher Education, 2016)
The following analysis sought to critically interrogate philosophical underpinnings which influence curricular design of academic literacy instruction in extended degree programmes (EDPs) with contextual focus given to the Introduction to Academic Discourse (IAD) course, a curricula requirement of the Commerce Extended Studies Programme (CESP) at Rhodes University. The methodology of the study included a comparative analysis of and analogical-application of mechanist, idealist and realist ontologies of inquiry towards understanding beliefs and ideologies which contribute to the choices of current, emergent models of academic literacy facilitation within EDPs. The results of the investigation highlighted that each, ontological lens proved effective as a theoretical framework for analysing foundational structures engaged in the facility of academic literacy practices. The study concluded by approaching academic-literacy implementation in the foundational domain within a social realist framework.